1999
DOI: 10.1094/cchem.1999.76.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Amylose and Amylopectin Interact in Retrogradation of Dispersed High‐Amylose Starches

Abstract: Cereal Chem. 76(2):282-291Retrogradation of three high-amylose starches (HAS: ae du, ae V, and ae VII) and common corn starch (CCS) was examined by dynamic oscillatory rheometry (7.5% [w/w] starch in 20% [v/v] dimethyl sulfoxide [DMSO]), differential scanning calorimetry (DSC; 30% [w/w] starch in water), and turbidity (0.5% [w/w] starch in 20% [v/v] DMSO). Nongranular lipid-free starch and starch fractions (amylose [AM], amylopectin [AP], and intermediate material [IM]) were studied. Gels were prepared by dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 45 publications
6
78
0
1
Order By: Relevance
“…A growing number of correlative studies over the past 2-3 decades imply that amylopectin structures with a higher proportion of long chains form harder gels, retrograde faster to decrease digestion rate, and make pastes resistant to shear-induced breakdown, which indicates greater intermolecular interactions among these long chains. While one theory holds that such structures have more flexibility for external chain interactions (Klucinec & Thompson, 1999), the present work suggests that the long internal chains could promote such interaction as well, perhaps forming double helical structures with external chains from other amylopectin molecules. Further work is needed to investigate more directly this possibility.…”
Section: Relevance To Starch Functionalitymentioning
confidence: 60%
See 1 more Smart Citation
“…A growing number of correlative studies over the past 2-3 decades imply that amylopectin structures with a higher proportion of long chains form harder gels, retrograde faster to decrease digestion rate, and make pastes resistant to shear-induced breakdown, which indicates greater intermolecular interactions among these long chains. While one theory holds that such structures have more flexibility for external chain interactions (Klucinec & Thompson, 1999), the present work suggests that the long internal chains could promote such interaction as well, perhaps forming double helical structures with external chains from other amylopectin molecules. Further work is needed to investigate more directly this possibility.…”
Section: Relevance To Starch Functionalitymentioning
confidence: 60%
“…Studies regarding the contribution of long chains of amylopectin to its functionality have focused on increased interactions among external chains of amylopectin (Cameron, Durrani, & Donald, 1994;Klucinec & Thompson, 2002;Klucinec & Thompson, 1999;Miles et al, 1985;Ring et al, 1987). Based on the theory of Thompson (1999, 2002), two types of junction zones can form during amylopectin retrogradation affecting their functionality: (i) intermolecular double helices from external chains termed as the Type 1 junction zone where external chains from two different molecules form double helices, and (ii) an intramolecular double helix could participate in a semicrystalline aggregate with double helices from a separate molecule, forming an intermolecular aggregate of double helices of external chains as the Type 2 junction zone.…”
Section: Introductionmentioning
confidence: 99%
“…Jenkins and Donald (1995) investigated the effect of varying amylose content on the internal structure of maize, barley and pea starches, and reported that amylose disrupts the structure order within the amylopectin crystallites. Klucinec and Thompson (1999) recently reported that each component interacts in retrogradation of dispersed starches. The difference of crystallinity may be attributed to the fine structure of each starch fraction of wheat grain.…”
Section: Resultsmentioning
confidence: 99%
“…A retrogradação é o processo pelo qual o amido retorna ao seu estado mais ordenado, após a gelatinização (KLUCINEC; THOMPSON, 1999). Durante a retrogradação, as moléculas de amilose formam associações de duplas hélices de 40 a 70 unidades de glicose, sendo que a amilopectina forma duplas hélices menores, devido às restrições impostas pela estrutura ramificada das moléculas e o comprimento das ramificações.…”
Section: Análises Dos Amidosunclassified